Are those really transformative learning outcomes? Validating the relevance of a reliable process. (20th February 2021) - Harder, Marie K.; Dike, Felix O.; Firoozmand, Firooz; Bouvrie, Nicole des; Masika, Rachel J.
Abstract: Transformative learning is considered a cornerstone for advances in sustainability, because transformative shifts in perspective will be necessary for humankind to transition towards it. The theory of transformative learning (TL) has been considered in hundreds of applied studies in diverse fields, yet it remains descriptive and unable to prescribe which conditions and processes could reliably produce TL outcomes. Here an in-depth case study is used to investigate a candidate process from another field and unknown to TL researchers (called WeValue InSitu ) which has been reported to regularly produce some forms of informally denoted 'transformative outcomes'. The goal is to determine if these formally qualify, because this would imply the standard WeValue InSitu process could be a reliable way to produce, and investigate, TL and TL outcomes (TLOs). Using grounded thematic open-coding of full transcripts of three sets of post-event interviews, compared against statements made prior to the event, it is shown unambiguously that four outcomes have formal TL nature, as shifts in meaning schemes, one of which developed into a wider shift of meaning perspective over three weeks. These findings indicate that the WeValue InSitu process can likely produce TLOs regularly and identifiably, offering a 'pedagogical laboratory' which can be used for systematic studies to link its sub-processes in detail to the TL outcomes it produces, allowing step-wise progress in theory-building. It also indicates that WeValue InSitu can be prescriptively applied, within its limitations such as maximum group sizes and specialist facilitators, to trigger TL in local groups of villagers, governance officers, environmental enthusiasts, community-based organizations and/or government committees, to become more focused and self-aware and more mobilized towards sustainability actions. This study thus opens the door to new research agenda in theory-building and applications of TL towards sustainability. Highlights: Transformative Learning nature of WeValue outcomes is demonstrated. Evidence of significant prior reports of TLOs from WeValue processes. WeValue can be a 'TL-laboratory' for systematic series of TL studies. WeValue can assist studies of TL processes, context, and durability. A limitation is WeValue 's current need for a specialist facilitator.